ANALISIS PENGARUH PENERAPAN METODE ARUS BIAYA PERSEDIAAN, NILAI PERSEDIAAN, PERPUTARAN PERSEDIAAN DAN GROSS PROFIT MARGIN TERHADAP MARKET VALUE PERUSAHAAN MANUFAKTUR TAHUN 2003 - 2006 - Abubakar Arif (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2009)
The aim of this research is to find the influence of inventory cost flow methods,inventory value, inventory turnover and gross profit margin to the company market value.The research data was gathered from the annually financial report 72 manufacturercompanies that were sampled listed on Jakarta Stock Exchange (JSX) within the period of2003 - 2006. Out of the 72 manufacturer companies, 21 companies implemented the FIFOinventory cost flow method and 51 companies implemented the average inventory cost flowmethod. These samples were chooses by applying the purposed sampling method andpooling data.The analysis was calculated by using normalization data test, classic assumptiontest consists of autocorrelation, heterocedacity and multicolinearitas. Afterwards,hypothesis test was measured by utilizing the multiple regression test followed with t testand F test also independents t test act as a support for hypothesis test.The result of this research shows that as collectively the inventory cost flowmethods, inventory value, inventory turnover and gross profit margin significantly affectedthe market value. Other while, the variables were inventory cost flow methods, inventoryturnover and gross profit margin had a less impact to the market value.